Land use and land cover dynamics in the Keleta watershed, Awash River basin, Ethiopia. (27th May 2019) - Bekele, Daniel; Alamirew, Tena; Kebede, Asfaw; Zeleke, Gete; Melesse, Assefa M.
ABSTRACT: Unprecedented pace and magnitude of land use/land cover (LULC) change in the Ethiopian highlands is a key problem threatening the natural ecosystem and creates vulnerability to an environmental hazard. A combination of remote sensing, field observations and focus group discussions were used to analyze the dynamics and drivers of LULC change from 1985 to 2011 in the Keleta watershed, Ethiopia. Supervised image classification was used to map LULC classes. Focus group discussions and ranking were used to explain the drivers and causes linked to the changes. The result showed rapid expansion of farmland and settlement (36%), shrublands cover shrinking by 50%, while the size of degraded land increased by 45%. Rapid population growth, rainfall variability and soil fertility decline, lack of fuelwood and shortage of cultivation land were ranked as the main causes of LULC change in the watershed according to the focus group discussion. Further effort is needed to improve the creation of new job opportunity, promotion of improved technologies to boost productivity and soil fertility, provide credit facility, extra push on irrigation infrastructure development and soil, water and natural ecosystem conservation practices. Generally, better community-based land resource management will need to ensure sustainable rural livelihoods.